Adaptations of Shakespeare’s Tragedies: A Comparative Study of Othello and Ahmed Yerima’s Otaelo - ABEGUNDE, Clement Tayo; DAVID, Seyitan Damilola (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Adaptation is one of the fertile grounds of literary scholars both in criticisms and writing. And there is no doubt that series of literary figures have succeeded in this both nationally and internationally. It is also an avenue for discourses and counter-discourses thereby engendering the scope of literature. Writers like Ola Rotimi, Femi Osofisan, Olu Obafemi among others have excelled in this regard making references to Western literary works intertextually to foreground their ideologies and the literary world in turn gives them attention. The purpose of the paper is to explore the adaptation of Shakespeare’s tragedy Othello by the Nigerian playwright, Ahmed Yerima and examine the intertextuality of Othello in the construction of Yerima’s Otaelo. The paper gives insights into the European and African cultural backgrounds of the two playwrights and their influences on the construction of both plays. It is thus discovered that the field of adaption in literary discourse helps to unravel lots of meanings in the original text of adaption and at the same time reflecting the socio-politcal and cultural tradition of the adopted culture. Therefore, this paper posits that postcolonial writers who parody European texts should not stop at just trying to rewrite the texts but find a means of making such works fit into African realities. There is no gainsaying about the fact that Armed Yerima, through improvisation, produced a play that successfully plants a European text on African soil.